Optimization Approach to Flat Slab Reinforced Concrete Building Frame Design - Mykytenko, Sergii; ., . (International Journal of Engineering and Technology, 2018)
In the article it is proposed to use optimization methods for the flat slab reinforced concrete frames design in order to reduce the reinforced steel and concrete costs during the construction. The use of flat slab reinforced concrete frames is a promising direction for providing citizens with affordable housing. It is proposed to implement rational design of flat slab reinforced concrete building frames using the methods of structural-parametric optimization and discrete-continuous mathematical programming. To solve the problem, conditional optimization methods are applied. The algorithm for calculating the frame of a multi-storey building has been developed. The algorithm is implemented by available means and does not require the creation of special computer programs. The author of the article implements a combination of discrete and continuous optimization methods for reinforced concrete structures calculation. This method application allows to design efficient flat slab reinforced concrete frames for the affordable housing construction.Â Â Â
Keywords: flat slab column conduit; reinforced concrete building frame; affordable housing; structural-parametric optimization.